Effects of post-traumatic stress syndrome in institutionalized adolescents in Romania - Enache, Rodica Gabriela; Matei, Raluca Silvia; Bîrsan, Sorina (Technium Social Sciences Journal, 2021)
The social events that have taken place in the last 30 years in Romania: the massive migration of the population abroad, the increase of the number of disintegrated families, the increase of the divorce rate; as well as political confusion, social problems, unemployment, insecurity, borderline situations, physical and psychological violence have led to an increase in the number of children, adolescents and young people who have suffered traumatic experiences. Our research aimed to describe the effects of post-traumatic stress syndrome in the case of institutionalized adolescents in Romania. Counselling for institutionalized adolescents to prevent post-traumatic stress disorder is required. Post-traumatic stress disorder (PTSD) causes an impediment to the personal development of adolescents, affects the quality of life, well-being, while distorting psychological comfort in schools.